(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Inability of fish farmers in Nigeria to produce at a rate that can meet the population demand has been linked to lack of access to crucial information on improved fish farming technique. Information is an indispensable factor in fish farming and it is the basis of extension service delivery. This study was designed to describe demographic characteristic of fish farmers, identify sources of various information to fish farmers and identify information access constraints faced by farmers. Purposive sampling procedure was used to select 2 States and a total of 160 respondents were selected for the study. Descriptive statistics such as frequency, percentage, mean and standard deviation and Chi-Square (X2) was used for inferential statistics. Result revealed that mean age was 44.8 years, 77.5% were male, only 7.5% have no formal education and 98.1% were full time fish farmers. About 25.0% received information frequently, 50.6% rarely while 24.4% never received information from extension agents. Inadequate of extension contact was identified by 88.8% of the respondents as information access constraint. Chi-Square analysis showed significant relationship (X2 = 13.426, p = 0.016) between source of information and utilization of information.